Evaluasi Kebijakan Sistem Zonasi di SMP Negeri Kabupaten Lampung Tengah - Anisa Sepina Ulfa; Romlah Romlah; Ahmad Fauzan (LP. Ma'arif Janggan Magetan, 2024)
This study aims to evaluate the implementation of the zoning system in public junior high schools in Central Lampung Regency using the CIPP (Context, Input, Process, Product) model. The research method used is qualitative with interview, observation, and documentation techniques conducted at SMPN 1 Terbanggi Besar and SMPN 1 Terbanggi Besar. Evaluation results show that in the context aspect, SMPN 1 is supported by a strategic location and adequate facilities, while SMPN 3 faces challenges due to its remote location and limited facilities. remote location and limited facilities. On the input aspect, SMPN 1 has better facilities and human resources than SMPN 3. On the process aspect, SMPN 1 managed to implement the zoning procedures effectively, although administrative administrative challenges remained, while SMPN 3 faced low interest from applicants. The product aspect showed that the zoning system in SMPN 1 helps to equalize education, while SMPN 3 needs more efforts to attract community interest.